2016
DOI: 10.15171/jnp.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Buffalo’s milk against toluene induced-nephrotoxicity in rats

Abstract: Background: Toluene is widely used in different activities of industrial, commercial and household applications. It can cause damage to the human body. Buffalos’ milk has a good nutritive value. Objectives: The aim of this study is to examine the negative effects of toluene on kidney tissues and to investigate the protective effects of buffalo’s milk against toluene-induced nephrotoxicity in rats. Materials and Methods: Forty adult male Wistar rats (180-220 g weight) were randomly assigned to eight groups (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…He suggested that the protecting impact of camel's milk could be related to its antioxidant capacity (32). The antioxidant property and protective effect of buffalo's milk on toluene induced nephrotoxicity were also reported (33). Our data showed that pretreatment of rats with buffalo's milk before to noise exposure diminished noise induced renal injury.…”
Section: Discussionsupporting
confidence: 60%
“…He suggested that the protecting impact of camel's milk could be related to its antioxidant capacity (32). The antioxidant property and protective effect of buffalo's milk on toluene induced nephrotoxicity were also reported (33). Our data showed that pretreatment of rats with buffalo's milk before to noise exposure diminished noise induced renal injury.…”
Section: Discussionsupporting
confidence: 60%
“…The association between food and health is well established. Recent overwhelming attention to plant products and traditional medicine has focused on natural antioxidant for preventing the tissues from various xenobiotics induced toxicities [13,14]. Atriplex halimus L. (Ah) is a famous halophytic shrub for the nutritive and energetic value, not only for livestock but also as food for nomads and the local steppe population.…”
Section: Introductionmentioning
confidence: 99%
“…Water buffalo milk is consumed in many countries. It contains high levels of vitamin A, iron, copper, phospho-rous, magnesium and other trace elements with antioxidant activity, as well (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…The animals of the third group were exposed to 100 dB noise for four hours daily within two consecutive weeks and the rats of the forth group were treated with 1 mL/d BM daily for two consecutive weeks (without noise exposure). The methods and amount of milk intake and also the selected sound intensity were based on the previous studies (12)(13)(14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%